2020
DOI: 10.1007/s11192-019-03332-4
|View full text |Cite
|
Sign up to set email alerts
|

Write better, publish better

Abstract: There is evidence that having more readable abstracts and introductions help authors get cited. I show that, in economics, there is also an effect of readability on the probability of publishing in a Top 5 journal (and in a higher-ranked journal in general). I compute readability measures for a set of working papers and examine the journals in which they get published. My results suggest that previous estimates of the effect on citations are downward biased, as higher-ranked journals are more widely read and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
0
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 11 publications
1
0
0
3
Order By: Relevance
“…When analyzed further, we found that these three journals are in the best quartile; Q1, which indicates high-ranking journals in this area. The high average number of citations may be due to the fact that higher-ranked scientific journals are more frequently read and cited than others [42]. The current findings corroborate the findings of López-Meneses et al [12].…”
Section: Discussionsupporting
confidence: 90%
“…When analyzed further, we found that these three journals are in the best quartile; Q1, which indicates high-ranking journals in this area. The high average number of citations may be due to the fact that higher-ranked scientific journals are more frequently read and cited than others [42]. The current findings corroborate the findings of López-Meneses et al [12].…”
Section: Discussionsupporting
confidence: 90%
“…Esses resultados ambíguos refletem a falta de consenso sobre a relação entre escore de legibilidade e qualidade estilística do texto. Fages (2020) associa boa legibilidade a mais downloads, citações e prêmios, mas Mubin, Tejlavwala, Arsalan, Ahmad, e Simoff ( 2018) compararam a legibilidade de artigos premiados e não-premiados no evento ACM Conference on Human Factors in Computing Systems e encontraram que os premiados têm menos legibilidade que os não-premiados. O próprio Kincaid reconheceu as debilidades das fórmulas de legibilidade e defendeu que servem como ferramenta de avaliação para revisão de texto, mas não são ferramentas de redação, nem devem ser usadas antes de haver um rascunho completo (McClure, 1987).…”
Section: Discussionunclassified
“…Como limitação, observe-se que o FRE é um indicador de qualidade de texto (Fages, 2020), mas um FRE maior não garante um texto melhor, nem substitui a análise perita do texto. Também não exploramos outros indicadores de legibilidade como os de Gunning, de Fry, de McLaughlin, entre outros (Wikipedia contributors, 2018).…”
Section: Estilo Científico E Métricas De Legibilidadeunclassified
See 1 more Smart Citation